Analisis Yuridis Tentang Efektivitas Komnas HAM dalam Penegakkan Hak Asasi Manusia Di Indonesia - Muhammad Fajar Lutfi Raihan; Muhammad Azka Zidane; Hendra Anie (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This study analyzes the effectiveness of the National Commission on Human Rights (Komnas HAM) in enforcing human rights (HAM) in Indonesia from a normative juridical perspective. The background highlights ongoing human rights violations up to 2024-2025, such as torture, conflicts in Papua, and religious intolerance, impacting public trust, national integration, and international image. Employing a normative juridical method with primary data (legislation) and secondary data (legal literature), the research identifies major obstacles including limited authority of Komnas HAM (investigation only, not prosecution), weaknesses in procedural law (application of KUHAP unsuitable for gross violations), poor inter-institutional coordination ("back-and-forth files" with the Attorney General's Office), resource limitations, and external factors like impunity and political intervention. The conclusion states that Komnas HAM's effectiveness is not yet optimal, with recommendations for legislative revisions, capacity building, and integrated mechanisms to strengthen independence and human rights enforcement.